Evolution vs. creationism in the classroom: The lasting effects of science education - Benjamin W. Arold (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Anti-scientific attitudes can impose substantial costs on societies. Can schools be an important agent in mitigating the propagation of such attitudes? This paper investigates the effect of the content of science education on anti-scientific attitudes, knowledge, and choices. The analysis exploits staggered reforms that reduce or expand the coverage of evolution theory in US state science education standards. I compare adjacent cohorts in models with state and cohort fixed effects and conduct fine-grained placebo tests to rule out scientific, religious and political confounders. There are three main results. First, expanded evolution coverage increases students' knowledge about evolution. Second, the reforms translate into greater evolution belief in adulthood, but do not crowd out religiosity or affect political attitudes. Third, the reforms affect high-stakes life decisions, namely the probability of working in life sciences.
Keywords: I28; J24; P16; Z12; 330; Evolution; religion; science education; human capital; beliefs; occupational choice